Involvement of the Soluble Urokinase Receptor in Chondrosarcoma Cell Mobilization. (14th December 2010) - Bifulco, Katia; Longanesi-Cattani, Immacolata; Masucci, Maria Teresa; De Chiara, Annarosaria; Fazioli, Flavio; Di Carluccio, Gioconda; Pirozzi, Giuseppe; Gallo, Michele; La Rocca, Antonello; Apice, Gaetano; Rocco, Gaetano; Carriero, Maria Vincenza
Abstract : High levels of urokinase receptor (uPAR) in tissue and serum of patients with chondrosarcoma correlate with poor prognosis. First, we analyzed the uPAR levels in tissues and plasma of five patients affected by chondrosarcoma. Interestingly, very high levels of uPAR and its soluble forms (SuPAR) were found on tumor cell surfaces and plasma, respectively, of two patients with lung metastases. Therefore, to investigate the role of SuPAR in chondrosaromas, we generated a primary cell culture from a chondrosarcoma tissue overexpressing uPAR on cell surfaces. We found that chondrosarcoma-like primary culture cells release a large amount of SuPAR in the medium. In vitro, SuPAR elicits chondrosarcoma cell migration likely through its uPAR88-92 sequence, since the DII88-183 or DIIDIIR88-284 uPAR domains retain motogen effect whereas DI1-87 or DIII184-284 domains, both lacking the uPAR88-92 sequence, are ineffective. Chondrosarcoma cells cross matrigel in response to SuPAR, and their invasion capability is abrogated by RERF peptide which inhibits uPAR88-92 signalling. These findings assign a role to uPAR in mobilizing chondrosarcoma cells and suggest that RERF peptide may be regarded as a prototype to generate new therapeutics for the chondrosarcoma treatment.